Cloning and Characterization of Gene Encoding Thermostable Enzyme from Domas Crater - Siti Julia Asyifa; Akhmaloka; Suharti (BENCOOLEN JOURNAL OF PHARMACY, 2022)
This research has been carried out an analysis of the gene encoding thermostable enzymes from natural samples of Domas Crater by using a metagenomic approach. The purpose of this study was to identify the gene encoded thermostable enzyme from natural samples of the Domas Crater. In this study, genes were amplified through random PCR technique from a collection of community DNA that had been isolated previously using a metagenomic approach. Random PCR of total community DNA produced DNA fragments with a size of about 1 kb, and then ligated to the pJET1.2/blunt vector and inserted into E. coli TOP10 for cloning process. The recombinant plasmid was then analysed using restriction enzymes BamHI and EcoRI to confirm the presence of the gene inserted in the cloning vector. Homology analysis of the DNA sequences of the cloned genes showed five groups of proteins that were similar to the ABC Transporter permease protein from archaea with an identity of about 76 – 96%. The grouping of these proteins is shown by the constructed phylogenetic tree.